A Multifactor Approach to Candidate Image. Issue 3 (26th May 2016) - Warner, Benjamin R.; Banwart, Mary C.
Abstract : Decades of communication research have demonstrated that political candidate images are important predictors of electoral success and that campaign communication influences these image perceptions. However, questions remain about the relative importance of various facets of candidate image, how electoral context and partisanship influence the salience of these facets, and whether privileged classes enjoy presumption in image facets that reinforce their dominant position in politics. These questions require a new approach to image research. We propose a multifactor approach that explores the relative importance of six image traits: character, intelligence, leadership, benevolence, homophily, and charm. The benefits of this approach are illustrated through application to two electoral contexts, the 2012 U.S. presidential election and the 2014 U.S. midterm elections.